Ca7Si2P2O16:Eu2+ green phosphor for optic enhancement of the WLEDs dual-layer remote structure - Van Liem Bui; Guo Feng Luo; Tam Nguyen Kieu (Institute of Advanced Engineering and Science, 2022)
To enhance the dual-layer remote phosphorus configuration’s color standard help spread its application in the LED devices, the new green-emitting phosphor of Ca7Si2P2O16:Eu2+ is proposed. The sol-gel method is used to dope the Eu2+ ions with Ca7Si2P2O16. Increasing the ion Eu2+ concentration can lead to high thermal stability, color-tunable ability, stronger green emission band, and higher photoluminescence extraction. The dual-layer structure’s color standards, as well as the luminous flux, are examined with different concentrations of Ca7Si2P2O16:Eu2+ in the phosphor layer. Owing to the improved features, the green phosphor Ca7Si2P2O16:Eu2+ has enhanced the emission intensity in the blue and green wavelengths, resulting in better color mixing and distribution. The luminescence shows the enhancement when increasing the concentration of Ca7Si2P2O16:Eu2+. However, the color rendering feature can present a reduction with more than 10% wt. green phosphor within the double-layer phosphorus remote configuration, due to color balance’s loss.